Struktura statystyczna polskiego systemu graficznego. Analiza historyczno-porównawcza - Osiewicz, Marek; Skibski, Krzysztof (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
This article presents a statistical and comparative analysis of four spelling conventions that represent different stages in the development of the Polish graphic system: the graphic system of a late-medieval manuscript (hand-written text), the standard spelling convention typical for the first half of the sixteenth century, the accepted and standard modern spelling of the first half of the twentieth century and the innovative set of graphic features used in electronic media. The characteristics of the statistical parameters encompasses dispersion and entropy in the first and the second row of letters, as well as in two-element sets (dyads). The analysis proves that: 1) inasmuch as the degree of differentiation of the distribution of signs, the history of Polish spelling convention prior to the solidification of the modern standard practice (accepted standard system) manifested a self-organizing tendency that was based on a reduction of letter signs and two-element letter combinations (ligatures) with the frequency of 1; 2) innovative solutions used in the set of graphic features characteristic for electronic media do not violate the statistical proportion between letters and their dyads operative and specific for modern standard graphic system 3) in respect to theory and information, the transformations of the graphic substance (graphic system) (within the analysed chronological timeframe) depended on neither progress (evolution) nor degradation.